Key Factors Affecting Lecturer Productivity To Conduct Research (International Journal of Scientific Research and Management (IJSRM), 2020)
The effectiveness of higher education institutions must be measured in terms of research productivity, the ability to produce new knowledge in the form of research and publications. In this case, lecturers as academic staff are expected to have a high level of capacity, commitment, integrity and responsibility to achieve the stated teaching and learning goals. Then, the global challenges that must be faced increasingly demand the role of lecturers to be able to further improve their work performance to conduct research and publish it in reputable international journals such as Scopus Idexed and others. Lecturers are one of the important factors for creating competent university graduates, and the main role of tertiary institutions is teaching, research and community service and is directed to expand knowledge and open new avenues of science and technology. This study aims to analyze the factors that influence the productivity of lecturers producing international scientific articles at Private Universities using Structural Equation Modeling. The data used are primary data by conducting surveys with a total of 310 respondents, and the analysis used includes validity, reliability, multiple linear regression, multiple tests, and hypothesis testing. The results showed that the positive direct effect of transformational leadership style and communication on lecturer productivity. Both of these exogenous variables, transformational leadership style has a path coefficient value of py1 of 0.201 and CR (tcount) of 3.715, while the communication variable proves to be the most dominant influence on productivity as an endegent variable, 5,132.